2010
DOI: 10.1111/j.1559-1816.2010.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Ingratiation and Self‐Promotion in the Selection Interview: The Effects of Using Single Tactics or a Combination of Tactics on Interviewer Judgments

Abstract: This paper investigates the relative effectiveness of the use of 2 impression‐management tactics—ingratiation and self‐promotion—on interviewers' evaluations of an applicant in a laboratory setting. It was suggested that the use of a single tactic would be better than the use of no tactic; that the use of self‐promotion would be more successful than the use of ingratiation; and, finally, that the use of a combination of tactics would lead to the best evaluations. Results were largely in line with our hypothese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 35 publications
(57 reference statements)
5
55
0
3
Order By: Relevance
“…The experiment constituted a 2 (self‐promotion: indirect vs. direct) × 2 (spatial distance: large vs. small) between‐subject design. The manipulations of these factors were implemented within the job interview video: Proost et al () used written extracts from a fictitious interview, which we adapted into scenarios; we then asked two semi‐professional actors to play the scenes as realistically as possible so we could film videos of the different conditions. All four scenes were played by the same two actors, both of whom had movie‐making experience and were employed in the hotel industry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment constituted a 2 (self‐promotion: indirect vs. direct) × 2 (spatial distance: large vs. small) between‐subject design. The manipulations of these factors were implemented within the job interview video: Proost et al () used written extracts from a fictitious interview, which we adapted into scenarios; we then asked two semi‐professional actors to play the scenes as realistically as possible so we could film videos of the different conditions. All four scenes were played by the same two actors, both of whom had movie‐making experience and were employed in the hotel industry.…”
Section: Methodsmentioning
confidence: 99%
“…Not all impression management tactics are equally effective. Relative to several other‐focused impression management tactics such as ingratiation, favor doing, and opinion conformity, empirical evidence in the context of job interviews points to the superiority of self‐promotion (Chen et al, ; Kacmar et al, ; Proost, Schreurs, De Witte, & Derous, ). Self‐promotion refers to self‐focused impression management behaviors whereby applicants try to appear competent by promoting their abilities and accomplishments (Stevens & Kristof, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some find coalition ineffective (Dosier et al, 1988;Falbe and Yukl, 1992;Kipnis and Schmidt, 1988); for example, Falbe and Yukl (1992) found that coalition is among the least effective tactics for influencing others and is seldom effective even when used with other tactics. Finally, we exclude the ingratiation tactic, because of the likelihood subjects would not respond honestly to questions about ingratiation (Proost et al, 2010). Thus, 5 of the eight tactics are omitted from the study leaving 3 influence tactics, namely rational persuasion, personal appeal, and exchange.…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…The majority (54.6 %) were junior students or elder. Their interview ratings were considered acceptable in selection experiments (Arvey and Campion 1982;Hazer and Jacobson 2003;Lievens and Peeters 2008;Rasmussen 1984;Posthuma et al 2002;Proost et al 2010) and valid due to their knowledge about the job requirements of the hotel industry. As such, our results based on students' ratings can, to high degree, be generalized to hotel managers.…”
Section: Participantsmentioning
confidence: 99%
“…In particular, as there are no commonly accepted résumé items and attributes across jobs and industries, previous research based on various contexts and research designs has offered hardly any generalized conclusions or managerial guidelines on hotel industry practices, and the relationship between preinterview judgments and postinterview decisions in the hotel sector remains unknown. During job interviews, in order to produce favorable judgments of their attributes, applicants often attempt to convey signals to interviewers by way of alternative influence tactics in order to control or manipulate the reactions of interviewers to images of themselves: that is, impression management (IM) (Ferris and Judge 1991;Gardner and Martinko 1988;Higgins et al 2003;Kacmar et al 1992;Kristof-Brown et al 2002;Proost et al 2010;Tsai et al 2005Tsai et al , 2010. This suggests that applicants' IM tactics with recruiters in an interview should influence the effect of résumé credentials on the chance of acceptance.…”
mentioning
confidence: 97%